Water‐Group Pickup Ions From Europa‐Genic Neutrals Orbiting Jupiter. Issue 9 (4th May 2022) - Szalay, J. R.; Smith, H. T.; Zirnstein, E. J.; McComas, D. J.; Begley, L. J.; Bagenal, F.; Delamere, P. A.; Wilson, R. J.; Valek, P. W.; Poppe, A. R.; Nénon, Q.; Allegrini, F.; et al.
Abstract: Water‐group gas continuously escapes from Jupiter's icy moons to form co‐orbiting populations of particles or neutral toroidal clouds. These clouds provide insights into their source moons as they reveal loss processes and compositions of their parent bodies, alter local plasma composition, and act as sources and sinks for magnetospheric particles. We report the first observations of H2 + pickup ions in Jupiter's magnetosphere from 13 to 18 Jovian radii and find a density ratio of H2 + /H + = 8 ± 4%, confirming the presence of a neutral H2 toroidal cloud. Pickup ion densities monotonically decrease radially beyond 13 R J consistent with an advecting Europa‐genic toroidal cloud source. From these observations, we derive a total H2 neutral loss rate from Europa of 1.2 ± 0.7 kg s −1 . This provides the most direct estimate of Europa's H2 neutral loss rate to date and underscores the importance of both ion composition and neutral toroidal clouds in understanding satellite‐magnetosphere interactions. Plain Language Summary: Jupiter's moons Europa, Ganymede, and Callisto all have icy surfaces which interact with their local environments. From this interaction, water‐group atoms and molecules are released from the icy surfaces and orbit Jupiter as a collection of material in "neutral toroidal clouds." The material in these toroidal clouds interact with the local charged particle environment, where neutrals in the toroidal clouds can become charged and incorporated into Jupiter's charged particle environment. Here, we highlight observations of Jupiter's charged particle environment and present the first detections of H2 + in this environment. These H2 + ions are shown to be originally produced from H2 lost from Europa and the abundance of detected ions allows us to determine Europa is losing 1.2 ± 0.7 kg s −1 of neutral H2 . This provides the most direct estimate of Europa's H2 neutral loss rate to date and underscores the importance of both ion composition and neutral toroidal clouds in understanding how satellites interact with their local charged particle environments. Key Points: First identification of H2 + in the Jovian magnetosphere from 13 to 18 R J, with a density ratio of H2 + /H + = 8 ± 4% H2 + in Jupiter's magnetosphere is predominantly produced by Europa's neutral toroidal cloud Europa's total H2 neutral loss rate is 1.2 ± 0.7 kg s −1